Virtual Reality Simulation Design For The Use Of Personal Protection Equipment For The Pertamina Refinery Area - Bayu Ramadhani Fajri; Azwil Danul Lailil Fitri; Yasdinul Huda; Asrul Huda; Janifan Christy (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Occupational safety and health are very important to pay attention to, especially for workers in the field. Personal protective equipment is a tool that can reduce the risk of work accidents. The Pertamina Company requires workers to carry out training on the use of personal protective equipment in Pertamina's demo room. The problem that often occurs is the limited space for conducting simulations if many workers take part in the training simultaneously, they have to queue first to enter the demo room. The final result of this research is to produce a virtual reality demo room application to save training time on the use of personal protective equipment. The stages in making the Virtual Reality demo room application include analysis, methods, design, development, and validation. The process of analyzing the Virtual Reality demo room application includes analyzing system requirements and using the waterfall method. The design of the virtual reality demo room application uses Unity and Blender software for 3D assets and animation. The Virtual Reality demo room application has passed the validation test stage in terms of media, software, and benefits obtained a score of 86.